Listening to young children : a guide to understanding and using the mosaic approach - Clark, Alison; Moss, Peter (Jessica Kingsley Publishers, 2017)
How can young children's views and experiences become the focus for reviewing quality in early childhood provision? Viewing children as 'experts in their own lives', the Mosaic approach offers a creative framework for listening to young children's perspectives through talking, walking, making and reviewing together.